2015
DOI: 10.1016/j.diagmicrobio.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogenic and enteroaggregative E. coli in stools of children with acute gastroenteritis in Davidson County, Tennessee

Abstract: This prospective acute gastroenteritis (AGE) surveillance was conducted in the inpatient and emergency room settings at a referral pediatric hospital to determine the prevalence of diarrheagenic Escherichia coli (DEC) in children<12 years of age with AGE in Davidson County, Tennessee. Subjects 15 days to 11 years of age, who presented with diarrhea and/or vomiting, were enrolled. Stool specimens were processed for detection of DEC using multiplex polymerase chain reaction. From December 1, 2011, to June 30, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 41 publications
0
14
2
1
Order By: Relevance
“…Our study reflected that EPEC constituted 54.0% of DEC isolates, a little higher than that reported by Yu et al [ 4 ], which supported the need for follow-up epidemiological studies in childhood diarrhea. EAEC strains have been associated with traveler’s diarrhea in both developing and industrialized countries [ 27 , 28 ]. Studies carried out in Brazil and Mexico revealed EAEC to be the primary pathotype, with respective rates of 50% [ 12 ] and 52.1% [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study reflected that EPEC constituted 54.0% of DEC isolates, a little higher than that reported by Yu et al [ 4 ], which supported the need for follow-up epidemiological studies in childhood diarrhea. EAEC strains have been associated with traveler’s diarrhea in both developing and industrialized countries [ 27 , 28 ]. Studies carried out in Brazil and Mexico revealed EAEC to be the primary pathotype, with respective rates of 50% [ 12 ] and 52.1% [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the proportion of aEPEC strains has increased, and aEPEC strains have outnumbered tEPEC strains and have also been associated with childhood diarrhea in some developing and developed countries 12, 18, 67, 91, 112, 129. However, the increase in prevalence of aEPEC may also reflect the refined discrimination between tEPEC and aEPEC 12, 18, 91…”
Section: Typical and Atypical Enteropathogenic E Colimentioning
confidence: 99%
“…aEPEC from sequence type (ST) 302 (serotype O108:H9) have been isolated from both healthy and diseased hosts, and the environment. They have been isolated from healthy pigs (Fröhlicher et al, 2008;Malik et al, 2017;Reid et al, 2017), water tanks in a poultry slaughterhouse (Alonso et al, 2014) and pork products made for human consumption (Lugsomya et al, 2018), and have been associated with diarrheic rabbits , pigs (Kleta et al, 2014), and humans (Foster et al, 2015). Yet to date, no genomic comparisons of E. coli ST302 strains, nor a complete ST302 genome, has been published.…”
Section: Introductionmentioning
confidence: 99%